Collaborative platforms as an opportunity to reach social innovation - Dieste Cobo, Juan Manuel (REVESCO. Revista de Estudios Cooperativos, 2020)
Social and sharing economy have some issues in common, like, sometimes, digital platforms. Both models have also a great complementary potential to create synergies and pursue its mutual strengthening. Perhaps sharing economy is faced with a major challenge in the coming years: to move towards a platform cooperativism model, in which digital platforms reflect the principles and values of cooperativism, or instead of, to be absorbed by the corporate economy, more interested in reduce costs and increase benefits through this platforms. Differences between these options are related to how the resources and goods are shared, the governance model adopted and the involvement of empowered citizens who are conscious of their role as producers, and not only as users or consumers. Therefore, the application of the cooperative values can contribute, not only to improved business performance and to reach cooperative governance, but also to make progress towards a new social and cultural paradigm, focused on promoting human and social development.
Keywords: Social economy; Sharing economy; Corporate sharing economy; Platform cooperativism; Digital platforms; Social innovation.